Armed Conflict dispossession of land and the cattle activity: An inXuiring between the unofficial testimony and the state numbers in the Department of 4eta Colombia - DUARTE ROJAS, Aura María; COTTE POVEDA, Alexander (Revista Iberoamericana de Estudios de Desarrollo)
This article studies the existent relationship between the armed conflict, the dispossession of land and the cattle activity in the municipalities of the Department of Meta in Colombia. Through cluster analysis, using regressions and the confrontation of the story of some victims of the armed conflict and the dispossession of land, it is possible to show the main findings of this investigation. The comparison among the diverse results indicates that the cattle activity and the spoil of land are related to the armed conflict. On the other hand, evidence has been found to reveal the relationship between the presence of armed groups, illegal crops and the unsteadiness of this Department’s social and economic development. Due to its effects through the time and its impact on the region, these last factors also affected negatively the social and economic development of each of the municipalities analyzed during the period from 2000 to 2009